Endoscopic laser treatment for urine leakage caused by an isolated calyx after robot‐assisted partial nephrectomy. Issue 6 (9th September 2021) - Inoue, Ryo; Isoyama, Naohito; Ozawa, Sho; Kobayashi, Keita; Yamamoto, Yoshiaki; Yano, Seiji; Hirata, Hiroshi; Matsumoto, Hiroaki; Matsuyama, Hideyasu
Abstract : Introduction: An isolated calyx is a rare complication in which the renal calyx and pelvis are disconnected. The treatment is often complicated. Case presentation: An 81‐year‐old man underwent robot‐assisted partial nephrectomy for the treatment of renal cell carcinoma (cT1bN0M0). Postoperatively, urine leakage was observed and did not improve with conservative measures. Retrograde pyelography and computed tomography revealed that urine leakage originated from the isolated calyx caused by infundibular stenosis. Endoscopic treatment via the transurethral approach was selected to preserve renal function. Ureteroscopy showed that the upper calyx was completely obstructed by the sutures. Therefore, we cut the suture thread using laser, and a ureteral stent was placed in the upper renal calyx. Fluid drainage immediately disappeared after the procedure, and the patient did not lose renal function. Conclusion: Endoscopic management might be an option for isolated calyx after robot‐assisted partial nephrectomy.